Personality and Motives for Social Media Use When Physically Distanced: A Uses and Gratifications Approach - Bowden-Green, Thomas; Hinds, Joanne; Joinson, Adam (Frontiers in Psychology, 2021)
This paper explores individuals’ motives for using social media when living under ‘social distancing’ conditions imposed during the COVID-19 pandemic, where they were instructed to physically distance from other people. Adopting a ‘uses and gratifications’ approach, and using a previously-established five-factor scale, we examine the relationship between individuals’ motives for using social media and their personality traits. 189 social media users living in the UK completed surveys assessing their motives for using social media and their personality. Our findings demonstrate that participants were generally motivated to use social media to ‘pass time’ and to ‘maintain relationships’. Further, we find that those high in extraversion in particular use social media to ‘maintain relationships’. By comparing our findings to previous studies where face-to-face interaction was not restricted, our findings indicate that individuals’ motives for using social media change when they are placed under physical distancing restrictions. We reflect on the potential application of our findings for others experiencing similar conditions, such as those working in remote locations, as well as the potential implications for living in a post-pandemic world with increased virtual ‘meetings’ using social media.